CHILDREN'S RIGHTS TO JUSTICE AND RESTORATIVE DIVERSION IN TERMS OF EFFECTIVENESS - Muzakir, Kahar (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2023)
Children in the context of law in Indonesia have different age limits. The Convention on the Rights of the Child stipulates that people are under the age of 18, including those in the womb as well as those who are married. This research method is descriptive analytical, to find restorative justice and diversion processes carried out by law enforcement officers in cases of children dealing with law (ABH) and see the effectiveness of Law Number 11. Criminal liability for children as a reference, that the implementation of diversion is also held as a alternative liability for criminal liability that meets the requirements of a restorative justice value. Diversion efforts are indeed not carried out by older perpetrators who commit serious crimes, because in practice, accountability for children from the results of diversion is often carried out by parents of child perpetrators, for example in terms of providing compensation for victims and obligations for people who are considered capable of educating children get better. A child who commits a serious crime (with a threat of more than 7 years) should act above the law in a child-friendly atmosphere, but still in the concept that the child perpetrator is not necessarily guilty, until it is proven legitimate and convincing. In principle, the concept of a restorative justice system has the aim of making perpetrators feel ashamed to commit crimes again.